2021
DOI: 10.1186/s12903-021-01396-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dental caries on oral health related quality of life among preschool children: perceptions of parents

Abstract: Background Childhood dental caries can affect the children’s and their parents’ oral health-related quality of life. The aim of the present study was to evaluate the impact of oral and dental health conditions on the oral health-related quality of life in preschool children and their parents. Methods In this descriptive-analytical cross-sectional study, samples were selected from children 3 to 6 years old enrolled in licensed kindergartens using "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
(39 reference statements)
3
17
1
2
Order By: Relevance
“…4 Such problems can lead to negative impacts on growth and development. 4,5 Further progression without treatment can lead to tooth loss, which will compromise the future of permanent dentition eruption and occlusion. 4,6 Other negative consequences include increased risk of hospitalizations and emergency visits, increased treatment cost, and loss of school days.…”
Section: Introductionmentioning
confidence: 99%
“…4 Such problems can lead to negative impacts on growth and development. 4,5 Further progression without treatment can lead to tooth loss, which will compromise the future of permanent dentition eruption and occlusion. 4,6 Other negative consequences include increased risk of hospitalizations and emergency visits, increased treatment cost, and loss of school days.…”
Section: Introductionmentioning
confidence: 99%
“…The mean DMFT and PUFA scores were significantly higher in the delinquent group compared to the mainstream group, suggesting a higher prevalence of dental caries in delinquent compared to mainstream children (26). Pakkhesal et al (27) concluded that the higher the DMFT score in preschool children, the more negatively impacted OHRQoL. Similar results were reported by Bukhari in working adults (28) and results were not comparable.…”
Section: Discussionmentioning
confidence: 80%
“…Oral health affects the oral cavity and the children's mental and physical status and appearance; it also affects their growth and development, speech, sense of taste, mastication, social relations, and establishing a sense of social satisfaction [1]. Oral health can be compromised by various factors, including traumatic dental injuries (TDI) and dental caries [2].…”
Section: Introductionmentioning
confidence: 99%